2018
DOI: 10.1093/dote/doy099
|View full text |Cite
|
Sign up to set email alerts
|

Wide-area transepithelial sampling with computer-assisted 3-dimensional analysis (WATS) markedly improves detection of esophageal dysplasia and Barrett's esophagus: analysis from a prospective multicenter community-based study

Abstract: Summary The 4-quadrant forceps biopsy (FB) protocol for identifying Barrett's esophagus (BE) and esophageal dysplasia (ED) suffers from poor sensitivity due to significant sampling error. We investigated the benefit of wide-area transepithelial sampling with 3-dimensional computer-assisted analysis (WATS) used adjunctively to the combination of random and targeted FB in the detection of ED, and as a secondary outcome, BE. In this multicenter prospective trial, community endoscopists at 21 sites util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…Using a random effects model, the relative increase in dysplasia detection was 48% (95% CI, 34%-60%%; I 2 Z 68%, Q Z 16). All heterogeneity in this analysis resulted from 1 study by Smith et al 105 Removing the study reduced I 2 to zero.…”
Section: Question 4: In Patients With Be Undergoing Endoscopy For Surmentioning
confidence: 99%
“…Using a random effects model, the relative increase in dysplasia detection was 48% (95% CI, 34%-60%%; I 2 Z 68%, Q Z 16). All heterogeneity in this analysis resulted from 1 study by Smith et al 105 Removing the study reduced I 2 to zero.…”
Section: Question 4: In Patients With Be Undergoing Endoscopy For Surmentioning
confidence: 99%
“…No study was poor in quality. Smith et al 19 contributed approximately greater than 60% of the data in this study 19 ( table 2 ).…”
Section: Resultsmentioning
confidence: 77%
“…58 A multicenter, community-based, prospective trial including 12,899 patients undergoing BE screening and surveillance found that using WATS3D as an adjunct to the Seattle protocol resulted in an absolute increase in dysplasia detection of 1.65% and an absolute increase in the rate of BE detection of 19.9%. 59 Another study showed that screening for BE is more cost-effective when WATS3D is used adjunctively to the Seattle protocol compared with the Seattle protocol alone. 60 The ASGE now recommends using WATS3D in addition to WLE for patients undergoing screening for BE.…”
Section: Wide Area Transepithelial Sampling With Three-dimensional Comentioning
confidence: 99%